Praktik Jual Beli Dengan Sistem Pre Order Perspektif Hukum Ekonomi Syari’ah (Studi Kasus Di Toko Online HelloByl_Aesthetic) - Izzan, Ahmad; Widaningsih, Santini; Syaripudin, Enceng Iip (STAI Al Musaddadiyah Garut, 2022)
Buying and selling is an activity of exchanging goods for property in the form of money. There are two types of buying and selling in practice, namely buying and selling directly and buying and selling indirectly. Direct buying and selling, for example, buying and selling in markets and minimarkets that directly meet to choose the goods to buy. While indirect buying and selling is done online, commonly known as Electronic Commerse (E-Commerse) which makes it easier for consumers to shop because consumers no longer have to come directly to the store, but only need to open a smartphone, open an online store and then buy the goods needed. The pre-order system or called PO is a selling system where a seller receives an order for a product offered on the marketplace media or social media. Toko HelloByl_Aesthetic is an online store (marketplace) that uses a pre-order system as an alternative in selling its products. This study aims to determine the pre-order buying and selling system in Islam. In addition, this study aims to find out the practice of buying and selling with a pre-order system carried out in HelloByl_Aesthetic online stores so that in the end the author wants to analyze the views of shari'ah economic law on the pre-order buying and selling system in HelloByl_Aesthetic online stores. Field research is a type of research used in this study, which is research where researchers directly look into the field to make observations of a phenomenon in a natural state. The phenomenon that is the object of study is the online store HelloByl_Aesthetic. The data collection techniques used were observation, interviews and documentation. From the data processed then analyzed using data analysis methods through the stages of data reduction, data presentation, and conclusions. The results of this study show that the practice of buying and selling with a pre-order system or ba'i salam carried out in online stores HelloByI_Aesthetic seen from the pre-order requirements, there are conditions that are not met, namely in the provision of goods to be sold are not yet available at the seller. When viewed from the point of view of sharia economic principles, it is in accordance with the principles of sharia economic law. Keywords: Buy and Sell, Pre Order, Ba'i Salam.